Strategy to Improve Food Security in Anticipation of Food Crisis in North Sumatera - Ningrum, Berlian Puspita; Hasibuan, Reni Ria Armayani; Daulay, Aqwa Naser (Newinera Publisher, 2025)
The purpose of this study is to analyze the food security strategy implemented by the North Sumatra Provincial Government in anticipation of the food crisis. This study will use a descriptive qualitative approach method through literature studies and interviews with the Food Security and Horticulture Service of North Sumatra Province. The sampling technique was carried out using Purposive Sampling. Data that has been collected from key informants and related institutions, then processed and analyzed through three steps, namely external factor evaluation, internal factor evaluation, and QSPM matrix. The results of the study show: Analysis of internal and external factors in the SWOT matrix, is positioned in Quadrant I by implementing the S-O strategy where strengths are used to take advantage of opportunities. The strategy is in the form of counseling to farmers so that they can improve their abilities and skills by collaborating between the agricultural service and the extension agency and collaborating with farmers to sell their harvest to Buloq Sub Drive North Sumatra with the aim of not importing food needs from outside so that the opportunity to become an independent region can be realized. Based on the SWOT analysis, eight alternative strategies were formulated to improve food security, with the main priority being to reduce the intensity of agricultural land conversion, increase collaboration between government agencies, and manage agricultural resources optimally. Other strategies include increasing access to agricultural product marketing, providing assistance for facilities and infrastructure by the government, and intensive assistance to farmers through counseling in each village.